Exploring parent-child relationships in families with advanced age parents: An interview study with adult offspring of ‘older’ parents in Switzerland - Nathalie Bettina Neeser; Andrea Martani; Kato Verghote; Bernice Simone Elger; Tenzin Wangmo (PLoS ONE, 2026)
In many societies, people are becoming parents at an older age. Although there is research on medical implications of advanced parental age (APA), little is known about the parent-child relationships and the lived experiences of offspring with APA parents. This study investigates these topics relying on semi-structured interviews with 20 adult offspring from Switzerland who have at least one parent that was 40 years old or older at the time of their birth. We performed an inductive thematic analysis. After completing the analysis, we found that the themes aligned closely with the theoretical model of intergenerational solidarity and therefore organized our findings in a manner informed by this framework. This allowed us to explore how the four conditional structures of solidarity this model identifies (opportunity, need, family and cultural-contextual) were perceived by our participants and featured in their conceptions of their parent-child relationships. We discuss our findings focusing in particular on the peculiarities that are related to the special dyadic relationship of our participants, i.e., one where parents are particularly old. Given that demographic trends of later-in-life childbearing are likely to continue, the results have implications on family building, (reproductive) ageing, parenthood norms and care arrangements for ageing parents.